Peningkatan Konsistensi Data dan Pengurangan Waktu Kerja Sistem Penilaian Karyawan - Raka Arba Puspa Darmayo; I Gede Agus Widyadana (Jurnal Titra, 2016)
Abstract: Performance of a company depends a lot on its employee’s performance. That causes many companies try so many ways to improve their employee’s quality and performance. XYZ company has a program that supports performance improvement named Continuous Improvement. In this program, there is a rating system which is applied to the machines the company have. These ratings will be reported to the machine operator. Machine that achieves its target will be declared as the winner and every employee that operates with that machine will be rewarded with bonus. However this system has a lot of problems especially in processing data. The occurring problem is, it takes a long time to process data and there are errors when employees are inputting the data. These problems become the background of this research. In this research, a proposal of a project that could decrease the time required to process the data and errors that occurs so that data’s consistency can improve will be given. The result of this project shows that the time required to process the data is reduced by 70% and human error can be avoided by making warnings and barricades.